SEMANTIC VARIETY OF VASYL STEFANYK'S LITERARY TEXTS - Kononenko, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The sphere of concepts of Vasyl Stefanyk’s creative work is considered through the system of semantic fields, the constant marking and the displacement of image and symbol. The meaning structures that are represented by the writer’s literary texts are classified as deeply-coded, internally transformed factors of discursive organization. The semantic paradigm is represented by the series of core word-concepts with the dominant, nucleus and periphery in their semantic, stylistic and evaluative differentiation.